Why trust you? Security cooperation within humanitarian NGO networks. Issue 1 (16th September 2019) - Schneiker, Andrea
Abstract : Although the literature is increasingly concerned with cooperation among humanitarian non‐governmental organisations (NGOs), we still lack studies that explain cooperation under conditions of competition. Drawing on 22 semi‐structured interviews, this article argues that trust is the driving force behind security‐related cooperation within networks of humanitarian NGOs. Which type of trust comes into play and how trust is built depends on the structure of a network. In small, stable networks, trust is typically based on experience, whereas shared identity is at the heart of trust in large, unstable networks. In the latter case, cooperation among humanitarian NGOs is exclusive and comparable to a form of club governance, because NGOs are kept out based on their identity—that is, if they adopt a different operational interpretation of the humanitarian principles.